2000
DOI: 10.1038/modpathol.3880078
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity with the Anti-MAGE Antibody 57B in Malignant Melanoma: Frequency of Expression and Correlation with Prognostic Parameters

Abstract: The melanoma-associated antigen (MAGE) family consists of a number of antigens initially recognized by cytotoxic T lymphocytes, which are currently being investigated for immunotherapy of patients with metastatic melanoma and other tumor types. Expression of MAGE mRNA in melanocytic tumors is said to be restricted to invasive malignant tumors and absent in nevi. Recently, a monoclonal antibody (57B) has become available to examine MAGE protein expression in archival material. In this study, we performed immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
2
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
(42 reference statements)
3
33
2
1
Order By: Relevance
“…Our findings are more in keeping with those of Brasseur et al (38), who reported MAGE-A1 in 48% of metastases and 16% of primary melanomas, although that study was based on reverse transcription-PCR analysis. Previous studies did not find a difference in expression of MAGE-A4 between primary and metastatic melanomas, and no correlation with stage or thickness could be established (39), although a correlation could be seen with the presence of an inflammatory infiltrate. However, the study consisted of fewer cases, and tumor and metastatic lesion were not derived from the same patients (39).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings are more in keeping with those of Brasseur et al (38), who reported MAGE-A1 in 48% of metastases and 16% of primary melanomas, although that study was based on reverse transcription-PCR analysis. Previous studies did not find a difference in expression of MAGE-A4 between primary and metastatic melanomas, and no correlation with stage or thickness could be established (39), although a correlation could be seen with the presence of an inflammatory infiltrate. However, the study consisted of fewer cases, and tumor and metastatic lesion were not derived from the same patients (39).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies did not find a difference in expression of MAGE-A4 between primary and metastatic melanomas, and no correlation with stage or thickness could be established (39), although a correlation could be seen with the presence of an inflammatory infiltrate. However, the study consisted of fewer cases, and tumor and metastatic lesion were not derived from the same patients (39). Likewise, few studies have looked at patterns of NY-ESO-1 expression in melanoma, although one smaller study did find NY-ESO-1 mRNA expression to be increased in metastases compared with primary samples (32).…”
Section: Discussionmentioning
confidence: 85%
“…In malignant melanoma, MAGE protein expression analyzed immunohistochemically with mAb 57B has been shown to correlate only with lymphocytic infiltrates, while no correlation was found with any other prognostic parameter. 47 On an mRNA level, correlation between CT antigen expression and tumor stage has been reported in several tumors such as renal cell carcinoma, 48 bladder 49 and esophageal carcinoma, 50 and melanoma. 51 This association has not been demonstrated in others: head and neck carcinoma, 52 seminoma 18 stomach, 53 or colon.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, melanocyte-specific antigens expression is of diagnostic value in some soft tissue lesions such as clear cell sarcoma, angiomyolipoma, and lymphangiomyomatosis (2). The increasing number of monoclonal antibodies (Mab) directed against formalin resistant melanoma associated antigens such as gp100 (HMB-45 Mab), Melan A (A103 Mab), CD63 (NKI/C-3 Mab), MAGE 1, MAGE 3, or tyrosinase (T311 Mab) has provided useful diagnostic tools (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, some melanocytic lesions lack most of these antigens, and non-melanocytic lesions may express melanocyte-related antigens (17)(18)(19).…”
mentioning
confidence: 99%